2022
DOI: 10.3390/ijerph192013686
|View full text |Cite
|
Sign up to set email alerts
|

Safety Management and Safety Performance Nexus: Role of Safety Consciousness, Safety Climate, and Responsible Leadership

Abstract: Drawing from social system theory, social identity theory, and social exchange theory, this study examines how safety management practices are linked with employee safety performance through safety consciousness and safety climate. Furthermore, responsible leadership is introduced as a boundary condition in the safety consciousness—safety performance and safety climate—safety performance relationships. Data were collected from employees belonging to pharmaceutical firms located in different industrial zones of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
(120 reference statements)
0
4
0
1
Order By: Relevance
“…From Table 3, the hypothesis that there is a significant impact of management commitment on the safety behaviour of healthcare workers shows that pvalue < 0.005 which is statistically significant and as a result is accepted. This finding is consistent with Garavan and O'Brien [2], Salem and Malik [18] and Pandit et al [19] who concluded that a major impact on safety behaviour was discovered by the safety climate in the form of ownership and involvement in safety as well as management commitment to safety. Amponsah-Tawaih and Adu [20] reported that workers complied with safety rules and procedures when they perceived safety communication and received training, which is an indication of the moderating role of management commitment to safety.…”
Section: Discussionsupporting
confidence: 89%
“…From Table 3, the hypothesis that there is a significant impact of management commitment on the safety behaviour of healthcare workers shows that pvalue < 0.005 which is statistically significant and as a result is accepted. This finding is consistent with Garavan and O'Brien [2], Salem and Malik [18] and Pandit et al [19] who concluded that a major impact on safety behaviour was discovered by the safety climate in the form of ownership and involvement in safety as well as management commitment to safety. Amponsah-Tawaih and Adu [20] reported that workers complied with safety rules and procedures when they perceived safety communication and received training, which is an indication of the moderating role of management commitment to safety.…”
Section: Discussionsupporting
confidence: 89%
“…Good leaders communicate with their subordinates. They give them guides and involve them in safety discussions and decision making [81]. This involvement keeps the workers engaged and makes them feel equally responsible for workplace safety.…”
Section: Safety Climate Influence On Safety Performancementioning
confidence: 99%
“…Por lo tanto, se requiere la provisión de capacitación a los trabajadores para aumentar y mejorar la conciencia de sus subordinados. Es por ello, que los estudios sugieren que la conciencia es un predictor importante de los comportamientos de seguridad y debe estar presente al realizar actividades laborales (Saleem & Malik, 2022).…”
Section: Gestión Y Conciencia De Seguridadunclassified